Virtuous giving : philanthropy, voluntary service, and caring - Martin, Mike W., 1946- (Philanthropic studies., 1994)
Philosophers have neglected philanthropy, dealing with it piecemeal or to illustrate abstract moral principles. Writing for the general reader, Mike W. Martin explores the philosophic basis of virtuous giving. After developing a unifying conception of philanthropy, Martin investigates a number of important questions. Does philanthropy express certain virtues? If so, what is their role? Is there a responsibility to engage in philanthropic activity? Do motives matter?